9514 1404 393
Answer:
57
Explanation:
Apparently, you want to simplify ...
![\displaystyle (1)/(√(2) + √(3) + √(7))](https://img.qammunity.org/2022/formulas/mathematics/college/7rko617pvfnhy9xm3wr0enlvq5ioeup51q.png)
so the denominator is rational. It looks like the form you want is ...
![(A√(2) + B√(3) + C√(7) + D√(E))/(F)](https://img.qammunity.org/2022/formulas/mathematics/college/xqp0vbvbii81yyfe5gflelm87q2bpuhdvz.png)
And you want to know the sum A+B+C+D+E+F.
__
We can start by multiplying numerator and denominator by a conjugate of the denominator. Then we can multiply numerator and denominator by a conjugate of the resulting denominator.
![\displaystyle =(1)/(√(2) + √(3) + √(7))\cdot(√(2) + √(3) - √(7))/(√(2) + √(3) - √(7))=(√(2) + √(3) - √(7))/(2√(6)-2)\\\\=(√(2) + √(3) - √(7))/(2√(6)-2)\cdot(√(6)+1)/(√(6)+1)=((1+√(6))(√(2)+√(3)-√(7)))/(10)\\\\=(√(2)+√(3)-√(7)+2√(3)+3√(2)-√(42))/(10)=(4√(2)+3√(3)-√(7)-√(42))/(10)](https://img.qammunity.org/2022/formulas/mathematics/college/jmre8b7iu8bneldl5tpc8u79e70uwra6p0.png)
Comparing this to the desired form we have ...
A = 4, B = 3, C = -1, D = -1, E = 42, F = 10
Then the sum is ...
A +B +C +D +E +F = 4 + 3 -1 -1 +42 +10 = 59 -2 = 57
The sum of interest is 57.